PATOGENESIS dan PEMERIKSAAN LABORATOPRIUM MIELOFIBROSIS PRIMER - Johanis Johanis; Arifoel Hajat (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Primary myelofibrosis (PMF) is a neoplastic hematologic disease, characterized by clonal hemapoietic stem cell and collagenaccumulation in bone marrow. PMF is not related with underlying myeloproliferative disorders or other diseases. The features of PMFshow marrow fibrosis, megakaryocytes and granulocytes proliferation, and extramedullary hemapoiesis. PMF is classified as BCR-ABLnegativemyeloproliferative disorders. Diagnosis of PMF is based on clinical symptoms of splenomegaly and myelopthisis; bone marrowbiopsy shows granulocytes/megakaryocytes hyperplasia, megakaryocytes dysmorphic and fibrosis; cytogenic testing for mutation ofJAK2V617F+, MPLW5I5L/K+ and BCR-ABL. The diagnostic criterion according to the 2008 WHO classification considers major andminor crieria. The primary purpose for treatment is to improve the quality of life by paliative tratment. The five year survival of PMFpatients is low.